The Rufous Sengi is not Elephantulus Multilocus reconstruction of evolutionary history of sengis from the subfamily Macroscelidinae - Krásová, Jarmila (Jihočeská univerzita, 2023)
We conducted multilocus phylogeny and divergence dating of sengis also known as elephant shrews from the subfamily Macroscelidinae. For the first time, we provided genetic evidence that the East African Rufous Sengi (Elephantulus rufescens) is closely related to the recently delimited genus Galegeeska known from the Horn of Africa and comprising a single species G. revolii. Our findings are in concordance with morphological traits and also biogeographical patterns known from Eastern Africa. Based on the results of divergence dating, the genus Galegeeska originated in the Pleistocene era.
The Rufous Sengi is not Elephantulus Multilocus reconstruction of evolutionary history of sengis from the subfamily Macroscelidinae
Keywords: sengis; elephants shrews; taxonomy; phylogeny; Eastern Africa; Galegeeska